When used together SS18–SSX fusion‐specific and SSX C‐terminus immunohistochemistry are highly specific and sensitive for the diagnosis of synovial sarcoma and can replace FISH or molecular testing in most cases. Issue 4 (12th September 2020) - Zaborowski, Matthew; Vargas, Ana C; Pulvers, Jeremy; Clarkson, Adele; de Guzman, Danica; Sioson, Loretta; Maclean, Fiona; Chou, Angela; Gill, Anthony J
Abstract : Aims: Synovial sarcoma is defined by recurrent t(X;18)(p11;q11) translocations creating SS18 – SSX1, SS18 – SSX2 or SS18 – SSX4 fusions. Recently, a novel rabbit monoclonal antibody designed to identify these fusions (SS18–SSX, clone E9X9V) was proposed to be highly specific (100%), but not completely sensitive (95%) for this diagnosis. Another antibody designed to identify the C‐terminal end of SSX (SSX_CT, clone E5A2C) was proposed to be highly sensitive (100%), but not completely specific (96%). We sought to validate these antibodies in an independent cohort. Methods and results: We performed immunohistochemistry for SS18–SSX and SSX_CT on 39 synovial sarcoma samples from 25 patients with confirmed gene rearrangements. Thirty‐four (87%) and 36 (92%) were positive for SS18–SSX and SSX_CT, respectively. False‐negative staining was associated with suboptimally handled small biopsies and decalcified specimens, even when staining was diffuse and strong in subsequent optimally processed excisions and non‐decalcified areas. None of 580 non‐synovial sarcoma tumours (76 whole sections, 504 TMA samples) were positive for SS18–SSX (100% specificity), whereas 39 (93% specificity) were positive for SSX_CT. Conclusions: SS18–SSX fusion‐specific IHC is 87–95% sensitive for the diagnosis of synovial sarcoma and highly (perhaps perfectly) specific. Therefore, positive SS18–SSX staining definitively confirms the diagnosis of synovial sarcoma. SSX_CT is less specific (93–96%) but highly sensitive (92%, but approaching 100% when suboptimally processed biopsies and decalcified specimens are excluded). Negative SSX_CT staining may therefore have an ancillary role as a rule‐out test for synovial sarcoma. We caution that both antibodies are prone to false‐negative staining in decalcified specimens.